A study on injuries of road traffic accident victims attending a tertiary care hospital, Tirupathi - P., Shakeer Kahn; N., Bayapa Reddy; C., Chandrasekhar; Altaf Hussain, R.; Reddy Jawahar Basha, K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Rapid motorization bought a boon along with the curse of road traffic accidents toll. Injuries and deaths due to road traffic accidents (RTA) are one of the major public health problems across the globe especially in developing countries due to lack of comprehensive legislative measures. It will have immeasurable impact on the families affected by RTAs. Methods: A hospital based, cross sectional study with victims of road traffic accidents admitted in S.V.R.R. Government General Hospital, Tirupathi, as study subjects was done during June 2013 to May 2014 for one year where 820 victims of road traffic accidents were interviewed after taking prior consent using a predesigned questionnaire. Results: External injury was seen in almost all cases (97.9%) and 61.5% suffered grievous injury. Laceration, fractures and abrasion are the most common types of injuries found. Regarding anatomical sites, head injury is the commonest (68.8%). Majority of the victims suffered grievous injury during 6AM to 12 PM (66.2%). The proportion of grievous injury was most commonly found in victims who were hit by Unknown vehicle (84.6%). Conclusions: Road side medical assistance by their timely action can prevent the toll of RTA fatalities and disabilities. Studies on injuries help in developing improved personal protective gear and safety measures inside the vehicles through novel engineering technology.